Water–saving irrigation combined with N–loaded clinoptilolite enhances nutrient yield, and water productivity by improving rice root characteristics: A combined PCA–SEM analysis - Yang Sun; Qi Wu; Daocai Chi; Hongyang Chen; Suyun Zhu; Qingliang Liu (Agricultural Water Management)
Nitrogen (N) –loaded clinoptilolite is renowned for its high–water retention and nutrient supplementation properties, which benefit crop growth. However, its combined effects with water–saving irrigation regime on N mineralization, root system characteristics, and nutrient yield, particularly their regulatory pathways, remain underexplored. This two–year split–plot experiment evaluated the impact of two irrigation regimes (ICF: continuous flooding irrigation; IAWD: alternate wet–dry irrigation) and two rates of N–loaded clinoptilolite (NZ0: no N–loaded clinoptilolite; NZ10: 10 t·ha–1) on root characteristics, mineralized N, nutrient yield, and water productivity. We employed principal component analysis (PCA) and structural equation modeling (SEM) to analyze the interactions among the factors. The IAWDNZ10 treatment showed the greatest water–saving potential, increasing the irrigated area by 0.29–fold compared to ICFNZ0. N–loaded clinoptilolite under IAWD increased root surface area by 12.6 %, average root diameter by 14.2 %, and root volume by 13.8 %. Additionally, IAWD increased mineralized N by 22.4 %, while N–loaded clinoptilolite further boosted it by 34.7 %. Root characteristics (r = 0.78) were crucial mediators in the effect of N–loaded clinoptilolite on protein (r = 0.64) and amylose nutritional yield (r = 0.68). Water usage influenced protein (r = -0.93) and amylose nutritional water productivity (r =-0.67) indirectly via chalky rice rate (r =0.90). In summary, integrating N–loaded clinoptilolite with the IAWD regime not only enhanced rice root characteristics and mineralized N but also led to substantial increases in nutrient yield and water productivity. These findings underscore the potential for N–loaded clinoptilolite to be adopted as a key component in sustainable agricultural practices, offering a pathway to optimize resource use, reduce environmental impact, and improve crop productivity in water–limited regions.